Forest Monitoring Using Remote Sensing Data and ILWIS GIS - Polina Lemenkova (Zenodo, 2015)
This paper focuses on the assessment of the changes in land cover types in Yamal peninsula over the past two decades, which shows local environmen- tal aspects of the climate change in North. Technically, the data processing was per- formed in ILWIS GIS, using semi-automated methods of image interpretation and supervised classification. The results of the classification analysis enable to identify changes in land cover types and their distribution in Yamal. P. Lemenkova. "Forest Monitoring Using Remote Sensing Data and ILWIS GIS". English and Russian. In: Recent Research Directions in the XXI Century: Theory and Practice. Proceedings of the International Conference (Voronezh State University of Forestry and Technologies n. a. G. Morozov VGLTU, Dec. 2–4, 2015). Ed. by V. M. Bugakov. Vol. 3.2. 9. Voronezh, Russia: VGLTU Press, 2015, pp. 346–350. doi:10.6084/m9.figshare.7210364. url: https:// elibrary.ru/item.asp?id=25116380.